Increase in Serum Ferritin Level as a Marker of Disease Activity in Pediatric Sys-temic Lupus Erythematosus (pSLE) Patients: Serum Ferritin Level as a marker of disease activity in pSLE - Desy Wulandari; Wisnu Barlianto; Susanto Nugroho; Tita Luthfia Sari (Journal of Tropical Life Science, 2023)
Ferritin is an acute-phase reactant that is elevated in autoimmune disorders, including systemic lupus erythematosus (SLE). However, their correlation with disease activity scores has not been confirmed. Pandemic Covid-19 makes children visitation to hospital to get the treatment of SLE were delayed. This study aimed to evaluate correlation between serum ferritin and disease activity and its role in screening for flare in pediatric SLE (pSLE) patients during pandemic Covid-19. This is a cross-sectional study conducted in Saiful Anwar General Hospital Malang. Sampling was carried out sequentially on pediatric patients who met the criteria for Systemic Lupus International Collaborating Clinics (SLICC) and were recorded between July 2021-May 2022. All patients were interviewed and assessed for disease activity using SLE Disease Activity Index 2000 (SLEDAI-2k). A score <4 was categorized as inactive disease. Biochemical, serological tests including markers of disease activity and ferritin level were measured by standard laboratory procedure. Comparison, correlation and ROC curve analyses were performed with SPSS software. There were 38 females pSLE participated in this study. The mean age of the patients were 12.6 ± 3.02 years. Serum ferritin significantly higher in active disease compared to inactive disease 84.50 ng/mL (68.00-151.75 ng/mL) ng/mL and 815.00 ng/mL (451.25-1570.00 ng/mL), a value of p<0.05 was determined to be statistically significant. A significant correlation was found between serum ferritin with SLEDAI 2K (r = 0.890, p = 0.000). Correlation was also found between serum ferritin and IgM anti-double stranded-DNA (r = 0.325, p = 0.046), but not with other laboratory and serological parameters. In ROC curve analysis, we found that Area Under The Curve (AUC) 0.989, 95%CI 0.964-1.014, p value 0,000, with cut off value 297.50 with sensitivity 85% and specificity 94.4%. Ferritin was increased in active disease   as compared to inactive disease and correlated with SLEDAI score and IgM-dsDNA. Thus, ferritin may be potential as an affordable and available marker of disease activity in pSLE during pandemic Covid-19.